2008
DOI: 10.1007/s00240-008-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of overweight and obesity on the urinary excretion of promoters and inhibitors of stone formation in stone formers

Abstract: In recent decades there has been an increasing prevalence of urolitithiasis in many western countries and at the same time there has been an increasing progression of obesity that has reached epidemic proportions. The aim of the present study was to assess the influence of overweight/obesity on the metabolic risk factors for renal stone formation. We studied 799 renal stone formers (462 men and 337 women) who came to the clinic for metabolic risk factors evaluation. They were all studied with a standard protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 18 publications
0
47
2
3
Order By: Relevance
“…The parallel growth in prevalence of obesity and morbid obesity over the past decades has increased the management of stone disease in this population (12,13). The association between urolithiasis and obesity is established in the literature and has shown that weight gain increases the urinary excretion of substances such as oxalate and uric acid, leading to stone formation (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…The parallel growth in prevalence of obesity and morbid obesity over the past decades has increased the management of stone disease in this population (12,13). The association between urolithiasis and obesity is established in the literature and has shown that weight gain increases the urinary excretion of substances such as oxalate and uric acid, leading to stone formation (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown an association among obesity, MS, and various urinary biochemical abnormalities recognized to increase the propensity for kidney stone formation (4)(5)(6). Greater body weight has been associated with lower urinary pH in stoneforming (7) as well as non-stone-forming individuals (8).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Lee et al analyzed a database of patient history, BMI, and serum and urine chemistry for 704 consecutive stone formers (467 first-time stone formers and 247 recurrent stone formers). Obesity was significantly associated with stone episodes (p ¼ 0.043).…”
Section: Obesity and Renal Stone Diseasementioning
confidence: 99%